Improved photocatalytic performance of cobalt doped ZnS decorated with graphene nanostructures under ultraviolet and visible light for efficient hydrogen production - Joan J. Kiptarus; Kiptiemoi K. Korir; David N. Githinji; Henry K. Kiriamiti (Scientific Reports, 2024)
Abstract Highly dispersed Cobalt doped ZnS nanostructures were successfully fabricated on the surfaces of graphene sheets via a simple hydrothermal method. X-ray diffraction (XRD), X-ray photocurrent spectroscopy (XPS), Raman spectroscopy (RS), Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) were utilized to analyze the structural characteristics of the cobalt doped ZnS decorated with graphene $${\rm Co}_x{\rm Zn}_{1-x}{\rm S}$$ Co x Zn 1 - x S rGO nanostructures (NSs). UV-visible optical absorption (UV-vis) studies were conducted to investigate their optical properties. In laboratory studies utilizing water and visible light, the photocatalytic activity of $${\rm Co}_x{\rm Zn}_{1-x}S$$ Co x Zn 1 - x S rGO NSs at (x = 0, 1, 2, 4 and 6 atm.%) were evaluated. Graphite Oxide (GO) was successfully transformed into sheets of graphene and $${\rm Co}_x{\rm Zn}_{1-x}{\rm S \, rGO}$$ Co x Zn 1 - x S rGO NSs possessed a crystalline structure according to the findings of XRD, RS and FTIR analysis. SEM investigation showed graphene sheets enhanced with ZnS NSs possessed cuboidal, spheroidal form of structure and displayed a paper like appearance. UV-vis confirmed a noticeable rapid increase in transmittance along the UV wavelength area and confirmed a highly transparent NSs in the wavelength range of (180-800 nm). Calculations using density functional theory (DFT) revealed that the Co NSs have more negative conduction bands than ZnS, allowing for effective electron transfer from cobalt to ZnS and exhibiting a band gap decrease as Co content increased. The $${\rm Co}_{0.04}{\rm Zn}_{0.96}S$$ Co 0.04 Zn 0.96 S rGO NSs sample had the highest photocatalytic activity, measured at $$7648.9 \, \upmu {\rm mol} \, {\rm h}^{-1}$$ 7648.9 μ mol h - 1 . A combination of improved dispersion properties, greater surface area, increased absorption and enhanced transfer of photogenerated electrons, $${\rm Co}_x{\rm Zn}_{1-x}S$$ Co x Zn 1 - x S rGO NSs increased the photocatalytic hydrogen generation activity.